Meta Warrick Fuller papers - Fuller, Meta Warrick, 1877-1968.
ALS (1950 May 15; Washington, D.C.) from Fuller to her nieces in Philadelphia, Pa., concerning an upcoming visit; and a copy of a photograph of Fuller removed from a publication (1938).
Sculptor.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Sculptors